2020
DOI: 10.1002/ctm2.195
|View full text |Cite
|
Sign up to set email alerts
|

Time‐restricted feeding improves the reproductive function of female mice via liver fibroblast growth factor 21

Abstract: Background: There has been a significant increase, to epidemic levels, of obese and overweight women of reproductive age, causing impairments to reproductive health. Time-restricted feeding (TRF) including isocaloric intake has shown to be preventive of obesity-related disorders. However, its therapeutic ability to improve the reproductive function of female remains largely unknown. Methods: Here, we investigated the ability of TRF to improve the reproductive function in wild-type and liver-specific FGF21 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 71 publications
(189 reference statements)
1
19
2
Order By: Relevance
“…Time-restricted feeding (TRF), defined as food consumed for ≤10 h per day, extends the time spent fasting and improves markers of metabolic health in both animal models (Froy and Miskin, 2010;Hatori et al, 2012) and humans (Sutton et al, 2018;Jones et al, 2020). In mammals, the improved health, metabolism, reproductive efficiency, brain signaling, and longevity were reported by many studies, with caloric intake similar to the ad libitum control group (Froy and Miskin, 2010;Hatori et al, 2012;Manoogian and Panda, 2017;Balasubramanian et al, 2020;Currenti et al, 2020;Hua et al, 2020). A global "experiment" in humans is Ramadan, a Muslim observance that consists of fasting from sunrise to sunset for a month: this practice has limited or no effect on body weight (BW) or body composition while improving blood lipid profile, insulin sensitivity, and other metabolic parameters; these beneficial physiological effects usually last beyond the Ramadan period (Osman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Time-restricted feeding (TRF), defined as food consumed for ≤10 h per day, extends the time spent fasting and improves markers of metabolic health in both animal models (Froy and Miskin, 2010;Hatori et al, 2012) and humans (Sutton et al, 2018;Jones et al, 2020). In mammals, the improved health, metabolism, reproductive efficiency, brain signaling, and longevity were reported by many studies, with caloric intake similar to the ad libitum control group (Froy and Miskin, 2010;Hatori et al, 2012;Manoogian and Panda, 2017;Balasubramanian et al, 2020;Currenti et al, 2020;Hua et al, 2020). A global "experiment" in humans is Ramadan, a Muslim observance that consists of fasting from sunrise to sunset for a month: this practice has limited or no effect on body weight (BW) or body composition while improving blood lipid profile, insulin sensitivity, and other metabolic parameters; these beneficial physiological effects usually last beyond the Ramadan period (Osman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…FGF21 was first discovered as a fast-response hormone [ 45 , 46 ], and was later observed to be induced by a variety of nutritional situations such as a low-protein diet [ 17 , 47 , 48 ], and a ketogenic diet [ 49 , 50 ], but not by caloric restriction [ 48 ]. In our previous research, we found that time-restricted feeding rescues female mice from body weight gain and glucose intolerance as well as from ovarian follicle loss and dysfunction of estrus cyclicity induced by a high-fat diet via liver FGF21 [ 13 ]. The different effects of MF and caloric restriction on FGF21 secretion, suggests that the beneficial effects of a lower MF are completely different from caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The freshly collected samples were then transported in solidified carbon dioxide and stored at − 80 °C until analysis. The SCFAs concentrations in the feces were analyzed through a gas chromatographic method as previously described [ 13 ]. Briefly, 0.7 g of fecal sample was suspended in 1.5 mL of distilled water, mixed, and allowed to stand for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E). In addition, timerestricted feeding improves the reproductive functions of female mice through liver FGF21 [31].Furthermore, FGF21 has bene cial effects, which implies that it is a vital positive regulatory factor of follicular development.…”
Section: Discussionmentioning
confidence: 99%